Factors affecting carotenoid levels in human plasma - Oshima, S. (Kagome Co. Ltd., Nishinasuno, Tochigi (Japan). Kagome Research Inst.); Kojima, F; Sakamoto, H; Ishiguro, Y (Nihon Eiyō, Shokuryō Gakkai shi, 1995)
We investigated factors which influence the plasma levels of major carotenoids in 76 healthy persons (54 males and 22 females), and also examined the correlation between plasma carotenoid levels and smoking or drinking habits. Significant sex differences were shown in plasma levels of xanthophylls, α-carotene and retinol. The correlation between the plasma level of carotenoids having provitamin A activity and the plasma level of retinol was strongly negative. All plasma carotenoid levels and the plasma α-tocopherol level showed a slightly positive correlation. On the other hand, plasma levels of triglyceride, total-, LDL- and HDL-cholesterol showed a weak correlation with plasma carotenoid levels. Smoking had a tendency to reduce the plasma levels of carotenoids, whereas drinking did not.